Creative Mindsets: Scale Validation in the Chinese Setting and Generalization to the Real Workplace - Zhou, Yiyong; Yang, Wa; Bai, Xinwen (Frontiers in Psychology, 2020)
Creative mindsets reflect the implicit beliefs individuals hold regarding the nature of creativity as innate (i.e., fixed mindset) or malleable (i.e., growth mindset). Karwowski (2014) developed the Creative Mindsets Scale (CMS) in which fixed or growth creative mindset was each measured with 5 items. Across three studies, the current study aimed to examine its psychometric properties in Chinese settings, and to explore to what extent effects of creative mindsets on creativity were generalized to the real workplace. Based on the survey data of 216 college students (Study 1) and 205 full time employees (Study 2) in China, results consistently indicated that a two-factor structure, in which both types of creative mindsets were independent with each other, was confirmed. Measures of both types of creative mindsets were of satisfactory psychometric features in terms of reliability (internal consistency) and validity (construct, convergent and discriminant validities). Furthermore, Study 1 provided evidence for the incremental validity of creative mindsets beyond mindsets of intelligence in explaining creative personal identity and creative self-efficacy. Based on a third independent sample consisted of 282 full-time employees from several Chinese companies, Study 3 further demonstrated that measures of creative mindsets could predict employees' creative performance as rated by their supervisors, lending additional support for its generalizability to the real workplace. Moreover, growth mindset, but not fixed mindset, was significantly related to creative performance, and such effect was mediated by effort. The present study contributed to the creative mindset literature by cross-validating CMS's psychometric properties in a new setting, and empirically establishing the link between creative mindsets and employees' creativity in the real workplace.